MIRZO ULUGH BEG’S PATRONAGE OF LITERATURE AND HIS ROLE IN THE CULTURAL LIFE OF FIFTEENTH-CENTURY TRANSOXIANA (The Journal of Interdisciplinary Human Studies, 2026)
In the development of world astronomy, medieval Eastern astronomy–particularly the scholarly activity of Central Asian scientists–occupies a special place. During this period, especially in the fields of the theory of the motion of the Sun, Moon, and planets, as well as practical astronomy related to determining time and geographical coordinates, Central Asian scholars, including Uzbek intellectuals, left a remarkably rich scientific legacy. At the same time, belles-lettres also underwent a significant stage of development. During the reign of Mirzo Ulugh Beg, literature flourished alongside the natural sciences in Samarkand and throughout Mawarannahr (Navoiy, 1997).
Keywords: Mawarannahr; belles-lettres; thinker; astronomy; literary gathering; scientific heritage; scholars; theory; practical astronomy; mathematics; and philosophy